Perspectives of children and young people with a sensory loss: opportunities and experiences of engagement in leisure activities - Hannah, Elizabeth Fraser Selkirk (Frontiers in Education, 2023)
Research indicates that engaging in leisure activities has a positive effect on the wellbeing, development, and quality of life of children and young people with disabilities. However, there appears to be limited literature focusing on the participation of children and young people with a sensory loss in leisure activities and few studies which have gathered data from children and young people. To address this gap, this study explores the perspectives of children and young people with a sensory loss (visual impairment and/or deaf) about opportunities to participate in leisure activities with other children/young people and their experiences. The research was conducted in one locality in Scotland. Sixteen children and young people with a sensory loss from primary and secondary schools participated in four virtual focus groups. Findings revealed that the participants enjoyed having opportunities to be with other children out with the school context. Psychosocial benefits from participation in leisure activities with other children with a sensory loss included feelings of not being alone and of being understood. Findings emphasized the lack of opportunities for children and young people with a sensory loss to engage in leisure activities in the community as well as barriers and facilitators to participation, such as communication. The study highlights the importance of increasing societal awareness of the needs of individuals with sensory loss and providing opportunities to engage in leisure activities in accessible environments.